Tumorigenic Effect of Thioacetamide in Swiss Strain Mice - Gothoskar, S. V. (Nature Publishing Group, 1970)
Male and female Swiss strain mice were put on a 0.03% thioacetamide diet at the age of 2 months. Control mice were kept on a stock diet. Control and treated mice were killed at the ages of 6, 9, 13 and 17 months. Progressive morphological, histological and biochemical alterations in the liver and tumour tissue of the treated mice were studied. In the 17-month-old group, 12 out of 13 treated mice developed hepatomas. IMAGES: